Platinum(II) complexes containing hydrazide‐based aminophosphine ligands: Synthesis, molecular structures, computational investigation and evaluation as antitumour agents. (21st April 2019) - Gholivand, Khodayar; Maghsoud, Yazdan; Kahnouji, Mohammad; Hosseini, Mahdieh; Satari, Mohammad; Abdolmaleki, Parviz; Roe, Stephen Mark
Abstract : Four new N, N ‐bis(diphenylphosphino)amine ligands (where amine = 1‐amino‐4‐methylpiperazine (L1 ), N ‐aminophthalimide (L2 ), 4‐aminomorpholine (L3 ) and hydrazine dihydrochloride (L4 )) and their Pt(II) complexes C1, C2, C3 and C4 were synthesized and characterized using infrared and NMR spectroscopies. The crystal structures of C1, C2 and C3 were determined using single‐crystal X‐ray diffraction techniques. The antitumour activities of the synthesized complexes determined using MTT assay on MDA‐MB‐231 cell line revealed that the studied complexes, especially C2, significantly suppressed the proliferation of these cancer cells in a dose‐ and time‐dependent manner (e.g. at a complex concentration of 100 μg ml −1, in 24 h, the reduction of the cell viability was 88.00, 38.89, 83.35 and 64.28% for C1 –C4, respectively). Theoretical approaches were also used to investigate the energy and the nature of metal–ligand and metal–chlorine interactions in the complexes, which could explain their biological activities. Results demonstrated that the interaction between ligand and Pt is stronger in C2, while the Pt–Cl interaction is weaker in this complex in comparison with the other complexes. Abstract : Synthesis of four bis(phosphino)‐amine ligands and their platinum(II) complexes have been reported. The complexes turned out to be useful as anticancer agents in the biological treatment. The nature of metal‐ligand and metal‐chlorine interactions have also been surveyed theoretically which successfully interpreted their biological activities.